2014
DOI: 10.2478/jos-2014-0044
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Nonresponse in Establishment Surveys: Using an Ensemble Tree Model to Create Nonresponse Propensity Scores and Detect Potential Bias in an Agricultural Survey

Abstract: Increasing nonresponse rates in federal surveys and potentially biased survey estimates are a growing concern, especially with regard to establishment surveys. Unlike household surveys, not all establishments contribute equally to survey estimates. With regard to agricultural surveys, if an extremely large farm fails to complete a survey, the United States Department of Agriculture (USDA) could potentially underestimate average acres operated among other things. In order to identify likely nonrespondents prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…Alternatively, researchers compare early and late respondents, use previous census information (e.g. Earp et al, 2014) or conduct costly non‐response surveys. With the rise of big data approaches, linking surveys with administrative data is gaining attention as a promising means to analyse non‐response bias (Bavdaž et al, 2020).…”
Section: Theory and Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, researchers compare early and late respondents, use previous census information (e.g. Earp et al, 2014) or conduct costly non‐response surveys. With the rise of big data approaches, linking surveys with administrative data is gaining attention as a promising means to analyse non‐response bias (Bavdaž et al, 2020).…”
Section: Theory and Backgroundmentioning
confidence: 99%
“…Alternatively, researchers compare early and late respondents, use previous census information (e.g. Earp et al, 2014) or conduct costly non-response surveys.…”
Section: Non-response Bias In Establishment Surveysmentioning
confidence: 99%
“…Ideally, the dropout propensity of sampling units in a panel study is even identified before unit nonresponse actually occurred. Then, respective counterstrategies can be devised that prevent dropout (see Earp et al, 2014). Moreover, identifying participation trajectories already early on in a panel study can help planning timelines for sample refreshments and evaluating budgetary requirements.…”
Section: The Problem Of Nonresponse In Longitudinal Surveysmentioning
confidence: 99%
“…Buskirk et al (2013) investigated the use of random forests for estimating response propensities, which were then applied to sampled units on subsequent cross-sectional surveys at later time points to estimate the propensity to respond. Earp et al (2014) investigated the use of a random forest-like ensemble of trees for evaluating nonresponse bias for establishment surveys. Buskirk and Kolenikov (2015) compared logistic regression and random forest models for nonresponse adjustments to sampling weights based on propensity scores.…”
Section: How Have Random Forests Been Used In How Have Random Forestsmentioning
confidence: 99%